The X factor: reflections on containment - Alastair Reid (Scottish Journal of Residential Child Care)
The X factor (Oxforddictionaries.com, n.d.) noun 1. a noteworthy special talent or quality: 'There are plenty of luxury cars around, but the S-Type has that special X factor.' 2. a variable in a given situation that could have the most significant impact on the outcome: 'The young vote may turn out to be the X factor.' Around a year ago I began an academic learning journey when I undertook to study for an MSc in residential child care. My initial goal when undertaking this was to be more effective in improving outcomes for the young people I worked with. Up until this point in my career, my practice development and understanding of my role as a residential worker had been shaped by a combination of observing experienced practitioners, short training courses, and trial and error. I observed individuals whose practice resonated with my own thoughts on positive practice and I tried to emulate them. Throughout my six years in residential care I have been lucky enough to work alongside a small number of individuals who seemed to have a magical 'X factor' within their practice that resonated calm, understanding and at the same time professionalism.